The association of physician-clinical pharmacist collaboration frequency and experience on physician burnout: are there gender differences - Jiang, Yuancheng; Zhang, Hongmeng; Wan, Chuchuan; Wu, Zonghao; Huang, Yuankai; Wang, Ennan (Frontiers in Psychiatry, 2025)
IntroductionBurnout is a widespread issue among physicians globally, with pronounced gender disparities observed in China. This paper aims to analyze the collaboration characteristics between clinical pharmacists and physicians in China, examine the impact of collaboration experience and frequency on physician burnout, and explore potential gender differences in these mechanisms to improve collaboration efficiency and reduce physician burnout. Collaboration experience was measured using the “Physician Experience” dimension from the Kuwait questionnaire. Collaboration frequency was assessed by asking physicians how often they collaborate with clinical pharmacists in their daily work.MethodsA cross-sectional study was conducted between July and August 2019 across 93 urban clusters in 31 Chinese provinces. The paper examined collaboration frequency and experience between physicians and clinical pharmacists in secondary and tertiary healthcare institutions, as well as physician burnout status. Data were analyzed using ordinal logistic regression models.ResultsA total of 1,381 questionnaires were distributed and 1,322 were included in the analysis. The results indicate that both the collaboration frequency and experiences between physicians and clinical pharmacists are negatively correlated with burnout. Additionally, gender shows an interactive effect in the negative relationships among collaboration frequency, collaboration experiences, and burnout. Specifically, the inclusion of gender as a variable weakened the negative correlation between collaboration frequency and the cynicism sub-dimension of job burnout. At the same level of collaboration experience, female physicians reported higher levels of cynicism and reduced personal accomplishment in job burnout compared to their male counterparts.ConclusionThis paper suggests that increasing collaboration frequency between physicians and clinical pharmacists, improving the collaborative experience, and paying particular attention to female physicians’ needs can better reduce physician burnout and improve healthcare service efficiency and quality.